2013
DOI: 10.1590/0001-37652013103512
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce adoption in Malaysian Small and Medium Enterprises Practitioner Firms: A revisit on Rogers' model

Abstract: The current climate of business necessitates competitions that are often tough and unpredictable. All organizations, regardless their size and scope of operation, are facing severe competitive challenges. In order to cope with this phenomenon, managers are turning to e-commerce in their respective organizations. The present study hinges upon exploring and explaining the different dimensions of the adoption of e-commerce among Small and medium enterprises, based on the Five Factors of Diffusion of Innovation Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Modern businesses often use online advertising and marketing, sell goods via the Internet, exchange business information electronically, and offer online auctions. Businesses relying on old methods alone are unlikely to survive 1 . Given the uncertain and turbulent economics, companies need to streamline their operations to reduce costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Modern businesses often use online advertising and marketing, sell goods via the Internet, exchange business information electronically, and offer online auctions. Businesses relying on old methods alone are unlikely to survive 1 . Given the uncertain and turbulent economics, companies need to streamline their operations to reduce costs.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing upon the theory of diffusion of innovation, Poorrangi et al 1 indicated that IT benefits, testability, top management support, resistant to change, culture, and IT complexity all affect e-commerce acceptance.Similarly, AlGhamdi et al 36 listed resistance to change, lack of clear rules in the field of social commerce, poor infrastructure, traditional ways of shopping, lack of confidence online, and lack of government regulation as the most important factors in the adoption of e-commerce. Tan et al 37 also studied the effective factors of adoption from the B2B perspective and indicated that limited access to computers, lack of trust, lack of a culture of sharing information across the organization, and an inability to deal with rapid changes are the most important factors inhibiting the adoption of e-commerce.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…management vision, perceived benefits, and management characteristics). Poorangi et al (2013) used Rogers' model (Diffusion and Innovation) to investigate the factors affecting the adoption of e-commerce in SMEs in Malaysia. The conceptual framework of their study was developed based on seven factors: relative advantage of innovation, observability, compatibility, trialability, complexity, management confidence, and employee resistance to change.…”
Section: Factors Enhancing and Inhibiting The Practice Of E-commercementioning
confidence: 99%